Impact of Dementia in Colorectal Cancer Patients: United States Population-Based Cohort Study - Thanathip Suenghataiphorn; Narathorn Kulthamrongsri; Pojsakorn Danpanichkul; Sakditad Saowapa; Natchaya Polpichai; Jerapas Thongpiya (The Korean Journal of Gastroenterology, 2024)
Background/Aims: Various socioeconomic and racial disparities are well-documented for colon cancer. However, the association of dementia, which is a growing cause of mortality in the elderly, remains unexplored. We aim to understand the association between these two conditions, in the elderly population group. Methods: We utilized the 2020 National Inpatient Sample to investigate records admitted for colorectal cancer identified through ICD-10 CM codes. We divided records by the presence of dementia. Adjusted odds ratios (aORs) for predefined outcomes were determined using multivariable logistic and linear regression models, adjusting for comorbidities. The primary outcome assessed was inpatient mortality, while secondary outcomes include other inpatient complications. Results: We identified 33,335 hospitalizations with ages more than 60. The mean age was 75.2 and males constituted 50.4%. In a survey multivariable logistic and linear regression model adjusting for patient and hospital factors, utilizing propensity score matching, the presence of dementia is associated with lower inpatient mortality (aOR 0.49, 95% confidence interval [CI] [0.26, 0.92], p=0.03), lower hospitalization costs (beta coefficient -2,823, 95% CI [-5,266, -440], p=0.02), lower odds of acute respiratory failure (aOR 0.54, p=0.01), lower mechanical ventilation usage (aOR 0.26, p<0.01) but higher odds of mental status change (aOR 1.97, 95% CI [1.37, 2.84], p<0.01). Conclusions: The presence of dementia is associated with a lower risk of inpatient mortality, and other clinical outcomes, in colorectal cancer cases admitted for hospitalization. Etiologies behind this relationship should be explored to understand this inverse relationship.